PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN JASA ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2012-2016 - Alien Adiartin Mulyani (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2016)
Debt policy is influenced by several factors including profitability and firm size.There are phenomenon in period 2012 until 2016 which showed that the increased of profitabilityand firm size but it is not followed by decrease of debt. The purpose of this research is to determine the effect of independent variables represented by profitability and firm size has influence on the dependent variable is debt policy on insurance companies listed in BEI period 2012-2016. The method is used in this research is descriptive method, verification with quantitative approach. The analytical method used is multiple regression. Besides previously also classical assumption which include normality test, test Multicollinearity, Heteroskidastity test and autocorrelation test. The results showed that there were no irregularities classical assumptions, it is shown that the available data has been qualified to use multiple linear regression models. The method of analysis used is multiple linear regression analysis with the help of analysis tools SPSS version 17.0 The result from this research indicate that profitability has a significant effect on debt policy, while firm size has no significant effect on debt policy. And simlutaneously profitability and firm size have a significant effect on debt policy. Keywords : Profitability, Firm Size, Debt Policy